2017
DOI: 10.1016/j.bone.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hedgehog antagonist delays but does not prevent fracture healing in young mice

Abstract: Fracture healing recapitulates many aspects of developmental osteogenesis. The hedgehog (Hh) signaling pathway, essential to skeletal development, is upregulated during fracture healing, although its importance is unclear. Our goal was to assess the functional importance of Hh signaling in endochondral fracture healing. We created closed, transverse diaphyseal femur fractures in mice, stabilized with an intramedullary pin, and administered a systemic Hh inhibitor or vehicle. Because Hh pathway activation is me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
1
33
1
1
Order By: Relevance
“…Baht et al found no effect on fracture healing when Hh signaling was genetically inactivated in chondrocytes, and concluded that the Hh pathway in chondrocytes was dispensable for fracture healing. Consistent with this, a previous study using Gli1 reporter mice found Hh activity in cartilagenous callus regions but more in the osseous callus regions . Moreover, treatment with a systemic Hh antagonist (GDC‐0449) had no effect on expression of chondrogenic genes during healing .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Baht et al found no effect on fracture healing when Hh signaling was genetically inactivated in chondrocytes, and concluded that the Hh pathway in chondrocytes was dispensable for fracture healing. Consistent with this, a previous study using Gli1 reporter mice found Hh activity in cartilagenous callus regions but more in the osseous callus regions . Moreover, treatment with a systemic Hh antagonist (GDC‐0449) had no effect on expression of chondrogenic genes during healing .…”
Section: Discussionsupporting
confidence: 90%
“…Yukata et al used a similar elderly mouse tibial fracture model, and attributed the blunted healing response to decreased proliferation and differentiation of periosteal stem cells. Similarly, compared to our recent data in 10‐week‐old vehicle‐treated mice, we found 18 mo mice had delayed radiographic bridging (80% fully bridged in 10‐wk mice at POD14, vs. 0% fully bridged in 18‐mo mice), and reduced callus density (169 mgHA/cm 3 at 10‐wk vs. 100 mgHA/cm 3 at 18‐mo) at POD14 compared to 10 wk mice. The healing deficiencies and clinical applicability of older rodent studies led us to use 18 mo mice for our healing‐challenged fracture study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations